(3GdhbGFY GdGbJUGOjI ef GdJGQjN GdbOje Edi HOGjI GdbQf GdhGMO hGdYTQhf (B/s - (3QGHM, HhbQIs; (3NHGHI, YHO Gddgs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2014)
(3GdhbGFY GdGbJUGOjI ef GdJGQjN GdbOje Edi HOGjI GdbQf GdYTQjf,GdhbGFY GdGbJUGOjI aj GdHdGO GdESdGejI bHd GdGSJYeGQ GdQCSeGdj,GdhbGFY GdGbJUGOjI GdeYGUQI,GdCReI GdGbJUGOjI heTcdI GdcSGO,GdJbdHGJ GdfbOjI heTcdI GdJVNe,EYGOI HfGA GdGbJUGOjGJ GdQCSeGdjI,HfGA GdGbJUGOjGJ GdGTJQGcjI,GdhbGFY GdGbJUGOjI aj EaQjbjG bHd GdGSJYeGQ GdQCSeGdj,GdYhdeI hGdCReGJ GdeGdjI,BKGQ GdYhdeI GdGbJUGOjI,GdCReGJ GdeGdjI(B:(3eaghegG hJOGYjGJgG,GdJfejI GdeSJOGeIs
(3HHdjhZQGajG(B:429-438s
Keywords: (3GdGbJUGOs